Ufudia, a replacement name for Pelonia Junker & Boomker, 2002 (Pentastomida: Sebekidae) from South African terrapins - Junker, Kerstin; Boomker, Joop (Zootaxa, 2016)
In order to accommodate a new species of pentastomid parasite, Pelonia africana Junker & Boomker, 2002 (Sebekidae), Junker & Boomker (2002) described the new genus Pelonia. This genus name is, however, preoccupied by Pelonia Grube, 1859 (Acari). Grube (1859) did not designate a type species, but Oudemans (1900: 141) recorded Pelonia as a possible synonym of Cepheus Koch, 1835 and listed P. foliosa as its type species, allegedly designated by Grube. Subías et al. (2012), accepted the synonymy of Pelonia with Cepheus Koch, 1835 (Acari: Compactozetidae). Norton & Ermilov (2014) provided a brief summary of the nomenclatural history of the mite genus Pelonia and proposed P. foliosa as being the nymph of Cepheus cepheiformis (Nicolet, 1855).